Direktorat Jenderal Sumber Daya dan Perangkat Pos dan Informatika (Ditjen SDPPI) - Odhi Pradana, Tantri; Lutfi, Achmad (Jurnal Ilmiah Administrasi Publik, 2025)
This research aims to explain how performance-based budgeting is implemented at Ditjen SDPPI. The Policy Implementation Model by Edward III (1980) is used as an analytical tool to describe the implementation of performance-based budgeting at Ditjen SDPPI using secondary data from the 2023 SPIP and SAKIP assessments. The results of this study show that in the implementation of performance-based budgeting at Ditjen SDPPI, there are significant challenges related to formulating objectives and performance indicators that comply with SMART criteria. The lack of integration between planning and budgeting, as well as the inability to utilize performance measurement results as a basis for budget adjustments, has caused gaps in achieving strategic goals. The 2023 SPIP and SAKIP assessments indicate that although there has been progress in planning and performance management, improvements in communication, bureaucratic restructuring, and enhancement of human resource competencies are needed to optimize the implementation of performance-based budgeting at Ditjen SDPPI.